In Silico Examination of Tinospora cordifolia Phytochemical Constituents towards Sars Cov-2, Dengue and Hepatitis Viruses by Molecular Docking Approach - Akhilraj, B. C.; Suresh, J.; Rajamani, K.; Kumar, M.; Gnanam, R.; Raghul, S. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during 2023 at Tamilnadu Agricultural University dept. of medicinal and aromatic crops. Tinospora cordifolia is considered valuable in terms of its immense medicinal properties. Medicinal plants containing phytochemical compounds are considered to be safer and non-toxic than synthetic medicines and in silico analysis of these phytochemical compounds is cost effective, rapid, helps to make decisions and simulate virtually besides useful in optimizing and refining long time experimental trials thereafter. Hence, the present study was mainly focused on in silico research of phytocompounds from T. cordifolia towards dengue, hepatitis A viruses and SARS-CoV-2. The compounds were docked employing AutoDock Vina in PyRx 0.8 a online screening system, onto the crystal patterns of SARS CoV-2 main protease (PDB ID- 2GZ9), dengue virus non-structural protein NS1 (PDB ID- 4OIG) and Hepatitis A virus 3C proteinase (1HAV). The ligands were shortlisted based on their hydrogen bond interactions and binding affinities. The top-ranking molecules showed the range‘s energy state of bonding of covid (-7.6 to -6.7 kcal mol-1), dengue (-7.9 to -7.3 kcal mol-1) and hepatitis (-8.0 to -6.9 kcal mol-1). Based on good binding energy, drug-likeness and efficient pharmacokinetics properties, it was evident that the compounds 3, 3-Dimethyl-1, 5, 13 , 14-tetraoxa-10, 19-diazacyclotricosane-6, 9, 20, 23-tetrone, tdnosporinone, and cordifolioside were conceived as possible deterrents for SARS CoV-2 main protease (Mpro), dengue virus non-structural protein NS1 and hepatitis A virus 3C proteinase respectively.